2015
DOI: 10.1590/1413-81232015208.11672014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity parameters as predictors of early development of cardiometabolic risk factors

Abstract: The scope of this study was to verify the association between different overweight and obesity parameters and the metabolic risk profile among school-age students. The randomized cross-sectional study included 1254 children and adolescents, aged 7 to 17, from a city in southern Brazil. Body mass index (BMI), waist circumference (WC) and percentage of fat (PF), measured at the triceps and based on subscapular skinfold thickness, were used as the parameters to evaluate overweight/obesity status. Systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
2
13
0
4
Order By: Relevance
“…Another important factor of the results is that the low levels of CF found in youth can be one of the main risk factors for cardiovascular events during adulthood 22 , proving this variable deserves attention during the years of adolescence. In addition, many studies have emphasized the prediction of risk factors for cardiometabolic health through CF in youth 10,13,23,24 . Therefore, this study points out an important result for cardiometabolic health in youth, with findings in agreement with a study of similar methodological characteristics 25 , using the same volume of exercise per week, progressively increasing the intensity of classes obtaining significant effects on CF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor of the results is that the low levels of CF found in youth can be one of the main risk factors for cardiovascular events during adulthood 22 , proving this variable deserves attention during the years of adolescence. In addition, many studies have emphasized the prediction of risk factors for cardiometabolic health through CF in youth 10,13,23,24 . Therefore, this study points out an important result for cardiometabolic health in youth, with findings in agreement with a study of similar methodological characteristics 25 , using the same volume of exercise per week, progressively increasing the intensity of classes obtaining significant effects on CF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity parameters include percentage of fat 39 , TG, TC 40 , ALT, AST 41 , leptin 42 , adipogenesis (SREBP-1, C/ EBPα, PPARγ) 43 , and lipogenesis related genes (SREBP-1, C/EBPα, LXRα) 44 . Ju et al 7 reported that SS reduced the mouse body weight, epididymal white adipose tissue weight, TG, TC, and leptin in the serum of HFD-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…A cross sectional study has established significant inverse associations with cardiorespiratory fitness and the clustering of metabolic risk factors in children (Machado-Rodrigues et al, 2014). Several studies have investigated the independent values of cardiorespiratory fitness, body mass index and waist circumferences for predicting cardiometabolic risk in children (Buchan et al, 2015;Burgos et al, 2015). The body mass index and waist circumference changes were most evident due to the clustering of cardiometabolic risk with body mass index, which is described as the main predictor in Brazilian children (Burgos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the independent values of cardiorespiratory fitness, body mass index and waist circumferences for predicting cardiometabolic risk in children (Buchan et al, 2015;Burgos et al, 2015). The body mass index and waist circumference changes were most evident due to the clustering of cardiometabolic risk with body mass index, which is described as the main predictor in Brazilian children (Burgos et al, 2015). This is consistent with strong to very strong associations found with body mass in the current study for total cholesterol (r = 0.72) and waist circumference (r = 0.94).…”
Section: Discussionmentioning
confidence: 99%